Recommendations on Arresting Global Health Challenges Facing Adolescents and Young Adults - Zohra S. Lassi; Rehana A. Salam; Zulfiqar A. Bhutta (Ubiquity Press, 2017)
Background: The health challenges faced by young people are more complex than adults and can compromise their full growth and development. Attention must be paid to the health of this age group, yet adolescents and youth remain largely invisible and often disappear from the major global datasets. Objective: The aim of this paper is to discuss the global health challenges faced by adolescents and youth, global legislations and guidelines pertaining to this particular age group, recommendations to arrest these challenges, and research priorities. Results: Major direct and indirect global health risks faced by adolescents include early pregnancy and childbirth, femicide, honor killing, female genital mutilation, nutritional habits and choices, social media, and peer pressure. There are no standard legal age cut-offs for adulthood; rather, the age varies for different activities, such as age of consent or the minimum age that young people can legally work, leave school, drive, buy alcohol, marry, be held accountable for criminal action, and make medical decisions. This reflects the fact that the existing systems and structures are focused on either children or adults, with very few investments and interventions directed specifically to young people. Existing legislation and guidelines need transformation to bring about a specific focus on adolescents in the domains of substance use and sexual behaviors, and the capacity for adolescent learning should be exploited through graduated legal and policy frameworks. Conclusion Sustainable development goals provide an opportunity to target this neglected and vulnerable age group. A multisectoral approach is needed to bring about healthy change and address the challenges faced by adolescents and youth, from modifications at a broader legislative and policy level to ground-level (community-level) implementations.